1994
DOI: 10.1055/s-0038-1642436
|View full text |Cite
|
Sign up to set email alerts
|

DX-9065a, a New Synthetic, Potent Anticoagulant and Selective Inhibitor for Factor Xa

Abstract: SummaryDX-9065a is an orally active newly synthesized and specific inhibitor for factor Xa. We have examined the property of DX-9065a in vitro and ex vivo. DX-9065a prolonged human plasma recalcification time, APTT and PT. Its doubling concentrations for clotting times of each coagulation assay were 0.49, 0.97 and 0.52 μM, respectively. Kinetic study revealed that DX-9065a inhibited competitively human factor Xa (Ki value: 41 μM). Ki values (pM) for other human serine proteases were as follows; thrombin >20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
148
0
2

Year Published

1995
1995
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(154 citation statements)
references
References 25 publications
4
148
0
2
Order By: Relevance
“…1). Daiichi compound DX9065a ((+)-2-[4-[((3S)-l-acetimidoyl-3-pyrrodinyl)oxy]phenyl]-3-(7-amidino-2-napthyl)propionic acid) exhibits a K~ of 41 nM for factor Xa, no activity against thrombin and displays some oral activity [11]. The inhibitor has been modelled to the active sites of factor Xa, thrombin and human trypsin [10,[12][13].…”
Section: Introductionmentioning
confidence: 99%
“…1). Daiichi compound DX9065a ((+)-2-[4-[((3S)-l-acetimidoyl-3-pyrrodinyl)oxy]phenyl]-3-(7-amidino-2-napthyl)propionic acid) exhibits a K~ of 41 nM for factor Xa, no activity against thrombin and displays some oral activity [11]. The inhibitor has been modelled to the active sites of factor Xa, thrombin and human trypsin [10,[12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The accompanying paper (8) demonstrates the differential actions on thrombin generation by two different anticoagulant protease inhibitors DX-9065a (9) and argatroban (10). Both theoretical and experimental approaches (8) revealed that the thrombin inhibitor, argatroban, yielded a stronger inhibitory effect on thrombin generation than the fXa inhibitor, DX-9065a, while the two inhibitors prolonged clot time to a similar extent when coagulation was triggered by the extrinsic pathway stimuli of the same intensity.…”
Section: Tafimentioning
confidence: 99%
“…Na química medicinal, muitas substâncias contendo este grupo funcional têm apresentado atividade contra vários agentes patogênicos como Giardia lamblia 5 , Leishmania sp [6][7][8][9] , Pneumocystis carinii [10][11][12][13][14] , Candida albicans 15,16 , Cryptococcus neoformans 15,16 , 17 , Trypanosoma sp [18][19][20][21] , Cryptosporidium sp 22 , Acanthamoeba polyphaga 23 e Plasmodium sp 24 . Além disso, o grupo amidina está presente em diversos compostos com atividade antitrombótica [25][26][27][28] . Na química de heterociclos, amidinas são intermediários muito utilizados nas sínteses de importantes sistemas [29][30][31] , tais como pirimidinas [32][33][34] , oxazóis 35 , triazinas 36 e tiazóis 37 .…”
Section: Introductionunclassified